Fernando Iwasaki’s Spain, Seventy Years after César Vallejo’s Spain - Tisnado, Carmen (Árboles y Rizomas, 2019)
España, aparta de mí estos premios [Spain, Take These Awards from Me] (2009) by Fernando Iwasaki establishes, no doubt, a connection to the well-known text by Peruvian poet César Vallejo, España, aparta de mí este cáliz[Spain, Take This Cup from Me]. This paper compares the lyric voice in Vallejo’s poem and the narrative voice in Iwasaki’s text. This comparison leads to an exploration of the way in which Spain is represented in two different historical times. In other words, what is the Transatlantic relation posed by Iwasaki? How can we compare this relation to the possible relation suggested by Vallejo? What views of Spain does Iwasaki represent in the narratives?